MULTIVARIANT AND UNIVARIANT INTERGROUP DIFFERENCES IN THE INVESTIGATED SPECIFIC MOTOR SPACE BETWEEN RESPONDENTS JUNIORS AND SENIORS MEMBERS OF THE MACEDONIAN NATIONAL KARATE TEAM - Kеnan Аsani; Vujica Živković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The aim is to establish intergroup multivariant and univariant investigated differences in specific motor space between respondents juniors and seniors members of the Macedonian karate team. The sample of 30 male karate respondents covers juniors on 16,17 and seniors over 18 years.In the research were applied 20 specific motor tests. Based on Graph 1 where it is presented multivariant analysis of variance Manova and Anova can be noted that respondents juniors and seniors, although not belonging to the same population are not different in multivariant understudied area.W. lambda of .19, Rao-wool R - Approximation of 1.91 degrees of freedom df 1 = 20 and df 2 = 9 provides the level of significance of p =, 16. Based on univariant analysis for each variable separately can be seen that has been around intergroup statistically significant difference in seven SMAEGERI (kick in the sack with favoritism leg mae geri for 10 sec.), SMAVASI (kick in the sack with favoritism foot mavashi geri by 10 sec.), SUSIRO (kick in the sack with favoritism leg ushiro geri for 10 sec.), SKIZAME (kick in the sack with favoritism hand kizame cuki for 10 sec.), STAPNSR (taping with foot in sagital plane for 15 sec.) SUDMNR (hitting a moving target with weaker hand) and SUDMPN (hitting a moving target with favoritism foot) of twenty applied manifest variables. There are no intergroup differences in multivariant investigated specific - motor space among the respondents juniors and seniors members of the Macedonian karate team. Based on univariant analysis for each variable separately can be seen that has been around intergroup statistically significant difference in seven SMAEGERI (kick in the sack with favoritism leg mae geri for 10 sec.), SMAVASI (kick in the sack with favoritism foot mavashi geri by 10 sec.), SUSIRO (kick in the sack with favoritism leg ushiro geri for 10 sec.), SKIZAME (kick in the sack with favoritism hand kizame cuki for 10 sec.), STAPNSR (taping with foot in sagital plane for 15 sec.) SUDMNR (hitting a moving target with weaker hand) and SUDMPN (hitting a moving target with favoritism foot) of twenty applied manifest variables.